Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Integrating genomic evolution and reported outbreak occurrence in foot-and-mouth disease in Asia: Cross-border lineage connectivity and exploratory prediction of reported outbreak occurrence - Xiaoyu Ge; Yize Li; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2026)

Effective strategy for simultaneous removal of Congo red and Cr(VI) by ferroan brucite - Shifeng Zhao; Xin Fan; Fengzhu Lv; Yanping Zhao; Yuli Cui (Journal of Water Process Engineering, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Quantification of sediment redox capacities under different Eh conditions by a modified electrochemical method - Yingxiao Tian; Peng Zhang; Yuxi Lu; Yanping Cui; Jinguang Xiao; Chenglong Yu; Songhu Yuan (Chemical Geology, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Urinary volatile organic compound metabolites and depressive symptoms among U.S. adults with cardiovascular-kidney-metabolic syndrome stages 0–3: NHANES-based associations and in silico multi-omics insights - Yulin Tian; Yiyun Wang; Hongsi Cui; Hongjie Wang; Yanping Yang; Yu Chang (NeuroToxicology, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Solar-driven degradation of HEDP and simultaneous phosphorus recovery from electroplating wastewater via a Cu (III)-mediated biochar electro-Fenton system - Shibo Zhao; Yanping Cui; Qiao Huang; Xian Xiang; Yuqing Qu; Chu Xiong; Bolin Li; Caixia Wen (Chemical Engineering Journal, 2026)

Numerical investigations on drag reduction by micro-bubbles of KVLCC2 ship model by means of OpenFOAM - Xiaojie Zhao; Yanping Hao; Jie Cui; Yichen Jiang (Ocean Engineering, 2025)

Improvement of electron transfer via anthraquinone-2-sulfonate addition to enhance volatile fatty acids production in anaerobic digestion system - Xiaoyue Li; Tingting Jiang; Huiyan Jing; Yue Cui; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2025)

Ammonium-activated peracetic acid for enhanced tetracycline degradation: Performance and mechanism - Qiao Huang; Yanping Cui; Bolin Li; Chu Xiong; Xian Xiang; Yuqing Qu; Shibo Zhao; Caixia Wen (Environmental Research, 2025)

Metabolic basis of resveratrol biosynthesis in P. megaterium PH3: Key roles of phenylpropanoid precursors and enzymatic feedback inhibition - Xiaohan Zhang; Dong Zhang; Junbo Liang; Liang Wang; Yanping Cui; Dingding Feng; Shuhong Ye (Food Chemistry, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

Removal of calcium from phosphoric acid produced by the nitric acid process using solvent extraction with TCHDGA and stripping with water - Chengjin Xu; Miaomiao Zhang; Jianhui Su; Xiujing Peng; Xiangfeng Kong; Yanping Luo; Jiahui Sun; Yu Cui; Xuchuan Jiang; Guoxin Sun (Hydrometallurgy, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Novel insight into the formation and improvement mechanism of physical property in fermented tilapia sausage by cooperative fermentation of newly isolated lactic acid bacteria based on microbial contribution - Qiaoyan Cui; Laihao Li; Hui Huang; Yanping Yang; Shengjun Chen; Chunsheng Li (Food Research International, 2024)

Chiral dual-core emitters based-on through-space coupling for high-performance OLEDs with little efficiency roll-off - Lifen Chen; Mingjia Deng; Shao-Yun Yin; Yu Fu; Yingxiao Mu; Jia-Xiong Chen; Lingyun Cui; Shaomin Ji; Yanping Huo; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Gold-copper-doped lanthanide luminescent metal-organic backbone induced self-enhanced molecularly imprinted ECL sensors for ultra-sensitive detection of chlorpyrifos - Yishan Fang; Yanping Li; Xufeng Zang; Yingxue Chen; Xinran Wang; Na Wang; Xiangying Meng; Bo Cui (Food Chemistry, 2024)

TCE degradation of modified graphite felt cathode in a flow-through electro-Fenton system and its H2O2 production ability in a real contaminated field - Yanping Cui; Haodong Yang; Xian Xiang; Shibo Zhao; Qiao Huang; Zhaoqiang Huang (Chemical Engineering Journal, 2024)

Fabrication of a straw-based degradable mulch film with magnetically controlled-release glyphosate - Dongqing Cai; Mengjia Cui; Linying Wang; Jinghong Ye; Xianghai Kong; Ruobing Mu; He Xu; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2024)

Intervention effects of fructooligosaccharide and astragalus polysaccharide, as typical antibiotic alternatives, on antibiotic resistance genes in feces of layer breeding: advantages and defects - Yanping Hu; Jingjing Wei; Yongze Yuan; Hongkui Wei; Yuanfei Zhou; Naidong Xiao; Juan Xiong; Zhuqing Ren; Jian Peng; Changzheng Cui; Zhongxin Zhou (Journal of Hazardous Materials, 2024)

Aquifer Water Abundance Evaluation Based on a Variable Weight Model - Aoshuang Mei; Qiang Wu; Keyao Han; Yifan Zeng; Pengfei Yang; Yanping Miao; Yang Lv; Yashuai Cui; Liang Yang (Mine Water and the Environment, 2024)

A novel antibacterial mechanism of atmospheric cold plasma against Staphylococcus aureus through degradation of cellular staphyloxanthin - Yupan Zhu; Hangbo Xu; Dongjie Cui; Renwu Zhou; Yanping Wang; Aswathi Soni; Gale Brightwell; Jie Zhuang; Ruonan Ma; Zhen Jiao (Innovative Food Science & Emerging Technologies, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Ca2+-dependent TaCCD1 cooperates with TaSAUR215 to enhance plasma membrane H+-ATPase activity and alkali stress tolerance by inhibiting PP2C-mediated dephosphorylation of TaHA2 in wheat - Minghan Cui; Yanping Li; Jianhang Li; Fengxiang Yin; Xiangyu Chen; Lumin Qin; Lin Wei; Guangmin Xia; Shuwei Liu (Molecular Plant, 2023)

Photocatalytic and oxidation mechanisms of Fe–Ag@AgCl: Effect on co-existing arsenic (III) and Escherichia coli - Yanping Cui; Qian Ye; Haili Wang; Xuewen Duo; Liang Peng; Wei Dong; Xiaoxiao Cui; Yue Lu; Yajie Li (Environmental Research, 2023)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Genome-wide identification of chicken bursae of Fabricius miRNAs in response to very virulent infectious bursal disease virus - Xuewei Huang; Yue Li; Xiaona Wang; Junyan Zhang; Li Wang; Han Zhou; Yanping Jiang; Wen Cui; Xinyuan Qiao; Yijing Li; Lijie Tang (Archives of Virology, 2022)

Analyses of the circadian clock genes expression in whole embryos and maternal major tissues of mice - Ximei Cao; Yindi Yan; Xuguang Luo; Xinhua Yang; Huilin Cui; Yanping Yang; Hairong Li (Journal of Molecular Histology, 2022)

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

Recombinant Avian β-Defensin Produced by Food-Grade Lactococcus as a Novel and Potent Immunological Enhancer Adjuvant for Avian Vaccine - Tingting Wang; Zhihao Wang; Jielan Mi; Wenqian Wang; Kai Li; Xiaole Qi; Yulong Gao; Li Gao; Changjun Liu; Yanping Zhang; Qing Pan; Xiaomei Wang; et al. (Probiotics and Antimicrobial Proteins, 2021)
In this study, we expressed rAvBD1-2–6-13 protein through Lactococcus lactis NZ3900, and the effects of the recombinant L. lactis NZ3900 as an immune enhancer and immune adjuvant were verified using in vivo and in vitro tests. In vitro tests revealed that recombinant L. lactis NZ3900 significantly activated the NF-κB signaling pathway and IRF signaling pathway in J774-Dual™ report cells and significantly increased the transcript levels of IL-10, IL-12p70, CD80, and CD86 in chicken PBMCs and chicken HD11 cells. In vivo experiments revealed that the immunized group supplemented with recombinant L. lactis NZ3900 as an adjuvant had significantly higher serum antibody titers and higher proliferative activity of PBMCs in the blood of the chickens immunized with NDV live and inactivated vaccines. Our study shows that the recombinant L. lactis NZ3900 has strong immunomodulatory activity both in vivo and in vitro and is a potential immune enhancer. Our work lays the foundation for the research and development of new animal immune enhancers for application in the poultry industry.

The Response Regulator MacR and its Potential in Improvement of Antibiotic Production in Streptomyces coelicolor - Meng Liu; Wenhao Xu; Yanping Zhu; Xiqing Cui; Xiuhua Pang (Current Microbiology, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Molecular evolution and pathogenicity of chicken anemia virus isolates in China - Yue Li; Nana Yan; Yongqiang Wang; Aijing Liu; Changjun Liu; Xingge Lan; Bo Yang; Yulong Gao; Honglei Gao; Xiaole Qi; Hongyu Cui; Kai Li; et al. (Archives of Virology, 2021)

Effects of Rhein-8-O-β-D-glucopyranoside on the Biofilm Formation of Streptococcus mutans - Yaochao Zhang; Yong Zhu; Yanping Zuo; Chengfang Tang; Fang Zhou; Xiaoming Cui; Lin Wang (Current Microbiology, 2021)

Research on the Establishment and Application of the Environmental Health Indicator System of Atmospheric Pollution in China - Qiong Wang; Liangzhong Li; Yanping Zhang; Qian Cui; Yuanzheng Fu; Wanying Shi; Qin Wang; Dongqun Xu (Bulletin of Environmental Contamination and Toxicology, 2021)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Visible light-activated 1-D core-shell paramagnetic Fe-Ag@AgCl as an innovative method for photocatalytic inactivation of E. coli - Yanping Cui; Nimesha Thathsarani; Liang Peng; Ya Gao; Lidan Lei; Zhengwei Zhou; Lili Liang; Xiaoyan Shi (Environmental Science and Pollution Research, 2020)

A novel compound wind speed forecasting model based on the back propagation neural network optimized by bat algorithm - Yanbin Cui; Chenchen Huang; Yanping Cui (Environmental Science and Pollution Research, 2020)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans - Xiaoxiang Yang; Hui Cui; Jiasen Cheng; Jiatao Xie; Daohong Jiang; Tom Hsiang; Yanping Fu (Environmental Microbiology, 2016)
Summary Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum . Previously, a conidiation‐deficient mutant, ZS‐1N22225, was screened from a T‐DNA insertional library of C. minitans . CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T‐DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino‐terminal citron homology domain and a central clathrin homology domain, as observed for other Vam6p/Vps39p family proteins. Abnormal fragmented vacuoles were observed in ΔCmVps39 under light microscopy and transmission electron microscopy, and ΔCmVps39 showed impairment in autophagy. ΔCmVps39 also exhibited significantly reduced hyphal development, poor conidiation and decreased sclerotial mycoparasitism. In addition, deletion of CmVps39 affected osmotic adaptation, pH homeostasis and cell wall integrity. Taken together, our results suggest that CmVps39 has an essential function in vacuolar morphology, autophagy, fungal development and mycoparasitism in C. minitans .

A single mutation in the PBC loop of VP2 is involved in the in vitro replication of infectious bursal disease virus - Xiaole Qi; Xiang Gao; Zhen Lu; Lizhou Zhang; Yongqiang Wang; Li Gao; Yulong Gao; Kai Li; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; et al. (Science China Life Sciences, 2016)

Detection of virus in CSF from the cases with meningoencephalitis by next-generation sequencing - Hongzhi Guan; Ao Shen; Xia Lv; Xunzhe Yang; Haitao Ren; Yanhuan Zhao; Yinxin Zhang; Yanping Gong; Peixiang Ni; Honglong Wu; Yicheng Zhu; Liying Cui (Journal of NeuroVirology, 2016)

Isolation and Characterization of a Novel Virulent Phage of Lactobacillus casei ATCC 393 - Xi Zhang; Yu Lan; Wenchao Jiao; Yijing Li; Lijie Tang; Yanping Jiang; Wen Cui; Xinyuan Qiao (Food and Environmental Virology, 2015)

Effect of amino acid sequence variations at position 149 on the fusogenic activity of the subtype B avian metapneumovirus fusion protein - Bingling Yun; Yanni Gao; Yongzhen Liu; Xiaolu Guan; Yongqiang Wang; Xiaole Qi; Honglei Gao; Changjun Liu; Hongyu Cui; Yanping Zhang; Yulong Gao; Xiaomei Wang (Archives of Virology, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Expression of biologically active human interferon alpha 2b in the milk of transgenic mice - Hui Li; Qingyou Liu; Kuiqing Cui; Jinfeng Liu; Yanping Ren; Deshun Shi (Transgenic Research, 2013)

Soil Respiration and N2O Flux Response to UV-B Radiation and Straw Incorporation in a Soybean–Winter Wheat Rotation System - Zhenghua Hu; Hailing Cui; Shutao Chen; Shuanghe Shen; Hanmao Li; Yanping Yang; Cenzi Li (Water, Air, & Soil Pollution, 2013)

Molecular cloning, expression profile, polymorphism and the genetic effects of the dopamine D1 receptor gene on duck reproductive traits - Cui Wang; Shijun Li; Chuang Li; Yanping Feng; Xiuli Peng; Yanzhang Gong (Molecular Biology Reports, 2012)